2016
DOI: 10.1128/aem.02578-15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Human Sapoviruses in Shellfish from Commercial Production Areas in Galicia, Spain

Abstract: The prevalence of human forms of Sapovirus, an emerging pathogen of human gastroenteritis, was investigated in an 18-month survey from class B mollusc-harvesting areas in two Galician rias (northwest Spain). The detection and quantification of Sapovirus was performed by reverse transcription-real-time PCR, according to the recently developed standard method ISO/TS 15216-1:2013, and genotyping by reverse transcription-nested PCR. The bivalve species studied were wild and cultured mussels (Mytilus galloprovincia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…; Varela et al . , ). Thus, 8 of 10 AiV positive samples from Ría de Area‐Betanzos showed in addition contamination with NoV GI (three samples) or GII (three samples).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Varela et al . , ). Thus, 8 of 10 AiV positive samples from Ría de Area‐Betanzos showed in addition contamination with NoV GI (three samples) or GII (three samples).…”
Section: Discussionmentioning
confidence: 99%
“…Bivalve molluscan shellfish are often associated with viral food‐borne disease (Vossen ) as they obtain their food filtering small particles suspended in water, being able to concentrate and retain pathogens including enteric viruses (Varela et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Thereafter, data on the occurrence of these viruses in aquatic environments have been accumulated rapidly within the past decade owing to development and/or improvement of PCR methods for the detection of these viruses in environmental samples (Kitajima and Gerba 2015;Oka et al 2015). Recent environmental studies carried out in multiple geographical regions have collectively demonstrated a high prevalence of both sapoviruses and AiV-1 worldwide (Kitajima et al 2010a(Kitajima et al , 2011aSano et al 2011;Fioretti et al 2016;Varela et al 2016;Haramoto and Kitajima 2017), indicating that these viruses might be more prevalent in the environment than previously appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…; Varela et al . ). A total of 78 samples including wild‐ and raft‐cultured Mediterranean mussels ( M. galloprovincialis ), Manila and carpet shell clams ( Ruditapes philippinarum and R. decussatus respectively) and cockles ( C. edule ) were collected from the same five harvesting areas from Moaña Bay in Ría de Vigo.…”
Section: Studies In Southern Ríasmentioning
confidence: 97%
“…; Varela et al . , ). Further studies are needed to determine their real importance for the public health in our region as well as to elucidate the role of bivalve molluscs as transmission vehicles of these pathogens, as suggested for SaV in Japan by Iizuka et al .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%